Mesh Network Based on MQTT Broker for Smart Home and IIoT Factory - Doan Huynh Mai Anh (Universitas Pendidikan Indonesia (UPI), 2022)
The Industrial Internet of Things (IIoT) provides connection among devices with the ability to monitor and exchange sensor data through the Internet. The need for reliability and high-quality data, as soon as possible that data monitoring able to afford the requirements from the IoT industrial standards. Recently, researchers have created more suitable communication protocols for IIoT devices, of which each has advantages such as XMPP, MQTT, AMQP in which MQTT is most widely used. This study proposes the utilization of MQTT as a communication protocol, which is one of the data communication protocols for IIoT. This work used temperature and humidity sensors, accelerometer sensors, current and voltage sensors because the digital and analog parameters are often needed as parameters of IIoT conditions. Data were scaled in real-time and stored in MySQL database. This study is also completed by mesh networks to deliver data from source to destination efficiently, these nodes using MQTT-based publish and subscribe. The result of this work demonstrates the transmission of data quality and reliability using MQTT protocol and the efficient power saving in mesh networks.